Healthcare Simulation Education Evidence, Theory and Practice - Nestel, D.; Kelly, Michelle; Jolly, B.; Watson, M. (John Wiley & Sons, 2017)
Containing examples of innovations from around the world, the book offers opportunities to make clear connections between the underlying rationale for the use of simulation, and what this looks like in practice.